IP multicasting : - Goncalves, Marcus (McGraw-Hill, 1999)
IP multicasting, companies can soon broadcast voice, video, and data over the Internet and Intranets without depleting network resources. This pioneering one-stop guide describes how IP multicasting works and what to expect in the next generation of Layer 3 switched networks. It also shows systems managers and network administrators how to implement multicasting products from 3Com, Ascend, AT&T, and dozens of other vendors within different network environments. Reflects the Internet Engineering Task Force's latest multicasting standards.